Abusive use of electronic cigarettes among healthcare students at a university in Paraná (Research, Society and Development, 2024)
Introduction: The sale, import and promotion of electronic smoking devices have been prohibited in Brazil since 2009. ANVISA recognizes that electronic smoking devices are classified as tobacco products, covered by the National Anti-Smoking Law. In Brazil, around 220,000 deaths per year are related to tobacco use, according to data from Fiocruz. However, the increased use of these devices may result in similar health consequences, especially when used excessively. Methodology: This research evaluated the incidence of electronic cigarette use among health students at Universidade Paranaense – Cascavel campus. This is a cross-sectional and original study, through the application of a questionnaire regarding the use of electronic cigarettes and adverse effects reported by students. The objective of the present study is to present the results of a survey on the abusive use of electronic cigarettes among university students in the health area. Results: 304 students participated in this research, and 82.9% were female. Of the data obtained, 73.4% (FA: 223) of the students claimed that they had already used electronic cigarettes, and of these, more than 60% were between 18 and 24 years old. Conclusion: There is a significant increase in the abusive use of electronic cigarettes among the young population.